2019
DOI: 10.1155/2019/7459236
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Microbiota on Diabetic Foot Wound in Comparison with Adjacent Normal Skin Based on the Clinical Features

Abstract: Diabetic foot ulcer (DFU) is a complication experienced by diabetic patients and does not heal well in an altered wound environment. Although diverse microbes in DFU were detected, little is known about their influences on diabetic foot wound (DFW) and the association with the skin microbiota in normal tissue from the same patients according to clinical features. We aimed to analyze the microbiota in normal skin and DFW tissue from the same subject and predict their roles based on clinical features. We analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 43 publications
3
30
0
2
Order By: Relevance
“…As a result and, in addition to those species described in Table 2, we found that the abundance of P. timonensis and Actinomyces turicensis related OTUs were increased in milk samples from mothers whose children developed CeD. In this regard, Peptoniphilus species have been considered as potential inducers of pro-inflammatory signals associated with an increased risk of suffering from human immunodeficiency virus (HIV) infection and wound severity in skin ulcers (Liu et al, 2017;Park et al, 2019), which could also confer higher susceptibility to other inflammatory conditions such as CeD. Moreover, breast abscesses caused by A. turicensis and Peptoniphilus harei also indicate these bacterial taxa are potentially pathogenic (Le Bihan et al, 2019).…”
Section: Discussionmentioning
confidence: 76%
“…As a result and, in addition to those species described in Table 2, we found that the abundance of P. timonensis and Actinomyces turicensis related OTUs were increased in milk samples from mothers whose children developed CeD. In this regard, Peptoniphilus species have been considered as potential inducers of pro-inflammatory signals associated with an increased risk of suffering from human immunodeficiency virus (HIV) infection and wound severity in skin ulcers (Liu et al, 2017;Park et al, 2019), which could also confer higher susceptibility to other inflammatory conditions such as CeD. Moreover, breast abscesses caused by A. turicensis and Peptoniphilus harei also indicate these bacterial taxa are potentially pathogenic (Le Bihan et al, 2019).…”
Section: Discussionmentioning
confidence: 76%
“…To analyze the microbiota in samples, metagenomic DNA was amplified following the 16S Metagenomic Sequencing library for the MiSeq system manufacturer’s guidelines (Illumina, San Diego, CA, USA), as described previously [ 21 , 22 ]. Briefly, the V1–V3 hypervariable regions of the 16S rRNA gene were amplified using primers with adapters (forward: 5′-adapter [TCGTCGGCAGCGTCAGATGTGTATAAGAGACAG]- GAGTTTGATCMTGGCTCAG-3′; reverse: 5′-adapter [GTCTCGTGGGCTCGGAGATGTGTATAAGAGACAG]-ATTACCGCGGCTGCTGG-3′).…”
Section: Methodsmentioning
confidence: 99%
“…In the 10 studies investigating patient characteristics, diabetes mellitus was investigated as a factor related to microbial diversity in wounds in seven studies. Indicators used included a diagnosis of diabetes mellitus (18,19), hemoglobin A1c (HbA1c) levels (11,(20)(21)(22)(23), and the duration of diabetes mellitus (20). Among them, both HbA1c levels and the duration of a patient's diabetes mellitus correlated with the alpha diversity index (dominance, p = 0.0174; diversity, p = 0.0168, the correlation coefficient was not shown) (20).…”
Section: Synthesis Of the Results Of Studies On Chronic Woundsmentioning
confidence: 99%